A simple method for industrialization to enhance the tap density of LiNi0.5Co0.2Mn0.3O2 cathode material for high-specific volumetric energy lithium-ion batteries. Issue 70 (11th July 2016) - Zhang, Yin; Wang, Zhen-Bo; Nie, Min; Yu, Fu-Da; Yun-Fei Xia,; Liu, Bao-Sheng; Xue, Yuan; Zheng, Li-Li; Wu, Jin
Abstract : The sample mixed with 9 μm, 6 μm and 3 μm (7 : 2 : 1) has a tap density of 2.57 g cm −3 and the specific volumetric capacity of 394.3 mA h cm −3 . And it has the advance of 8.5%, 22.2% and 40.6% than 9 μm, 6 μm and 3 μm, respectively. Abstract : Electrode materials with high tap densities and high specific volumetric energies are the key to large-scale industrial applications for the lithium ion battery industry, which faces huge challenges. LiNi0.5 Co0.2 Mn0.3 O2 cathode materials with different particle sizes are used as the raw materials to study the effect of the mass ratio of mixed materials on the tap density and electrochemical performance of mixed materials in this work. Physical and electrochemical characterizations demonstrate that the tap density of mixed powders with different particle sizes is higher than those of materials with a single particle size. The tap density of as-prepared material has a decreasing trend with the increase of the ratio of 9 μm sized particle in the materials. The highest tap density among all of the kinds of materials reaches up to 2.66 g cm −3 . Besides, the mixed material with a mass ratio of 7 : 2 : 1 has a bigger specific surface area and it presents better cycle behaviors and rate capability than other materials. The specific volumetric capacity of this mixed sample reaches up to 394.3 mA h cm −3 with 1C rate charge/discharge, and it has improvements of 8.5%, 22.2% and 40.6% over any single particle size of 9 μm, 6 μm and 3 μm, respectively, which contributes to the industrial production of Li–Ni–Co–Mn–O cathode materials for lithium ion batteries.